Barriers to Timely Treatment of Undescended Testis in Pakistani Patients: Why Are We Facing Delayed Presentation - Nawazish Ali; Jawairia Nawaz; Furqan Ullah khan; Shah, Muhammad Junaid; Iram Bashir; Muneeba Attique; Muhammad Arshad; Osama, Mohammad (Pakistan Armed Forces Medical Journal, 2026)
Objectives: To explore delayed presentations of cryptorchidism, factors responsible for the delay, and identify modifiable factors, providing region-specific evidence to guide clinical practice and public health interventions.Study design: Prospective observational study.Place and Duration of Study: Surgical Unit, MTI Gomal Medical College, Dera Ismail Khan, Pakistan from Oct 2024 to Mar 2025.Methodology: Data were collected regarding demographic, age at 1st diagnosis, cause of delay in treatment, socioeconomic status, parent’s literacy, laterality and palpability. Patients were grouped into three categories, namely, delay in early diagnosis, delayed referral for treatment and delay due to parents. Data were entered and analysed using Statistical Package for Social Sciences (SPSS), with appropriate descriptive and analytical statistics applied.Results: Total of 50 patients presenting to the surgical department during the study duration were analysed. Mostly coming from rural areas, majority of patients’ parents were uneducated, and majority of patients were from low socioeconomic background. The mean age at presentation for surgical procedure was 12.7+ 3.4 years. 45(90%) patients’ diagnoses were delayed.  Factors for delayed presentation, majority of patients were from rural areas with delay in diagnosis with p value= 0.258. Socioeconomic status of patients was mostly from the low 24(48%) and average 26(52%) ..Conclusion: Among 50 patients with undescended testis, 45(90%) had delayed early diagnosis (mean age 12.7 + 3.4 years); delays were multifactorial, highlighting the need for early screening, referral improvement and public health interventions.